2009
DOI: 10.4148/2378-5977.6780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing feeding level during late gestation on sow and litter performance (2009)

Abstract: . Brand names appearing in this publication are for product identification purposes only. No endorsement is intended, nor is criticism implied of similar products not mentioned. K-State Research and Extension is an equal opportunity provider and employer. Effects of increasing feeding level during late gestation on sow and litter performance Abstract A total of 108 gilts and sows (PIC 1050) and their litters were used over 2 gestation and lactation periods to determine the effect of increasing late gestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…(), individual piglet weights were increased (1.48 vs. 1.44 kg) after feeding 1.36 kg extra feed per day from day 90 to farrowing (Cromwell et al., ). This effect was observed in both gilts and sows, which is in contrast to a more recent study in which 0.91 kg extra feed per day was offered during the same period (Shelton et al., ). In the latter, individual piglets' birthweight was increased in gilts (1.42 vs. 1.51 kg), but decreased in sows (1.54 kg vs. 1.43 kg).…”
Section: Maternal Nutrient Provision Influences Piglets' Birthweight contrasting
confidence: 92%
“…(), individual piglet weights were increased (1.48 vs. 1.44 kg) after feeding 1.36 kg extra feed per day from day 90 to farrowing (Cromwell et al., ). This effect was observed in both gilts and sows, which is in contrast to a more recent study in which 0.91 kg extra feed per day was offered during the same period (Shelton et al., ). In the latter, individual piglets' birthweight was increased in gilts (1.42 vs. 1.51 kg), but decreased in sows (1.54 kg vs. 1.43 kg).…”
Section: Maternal Nutrient Provision Influences Piglets' Birthweight contrasting
confidence: 92%
“…Cromwell et al (1989) observed a 40-g increase in piglet birth weight when gilts and sows were fed an extra 1.4 kg of feed daily during late gestation. Shelton et al (2009) and Soto et al (2011) observed an increase in piglet birth weight in litters from gilts fed increased amount of feed during late gestation, although this was not apparent in sow litters. Yet the effects of increased feed allowance during late gestation on piglet birth weight remains unclear for commercial conditions, particularly in high-performing herds (>14.5 total piglets born/sow).…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing feed intake in late gestation has been shown to improve piglet birth weight (Cromwell et al, 1989;Shelton et al, 2009;Soto et al, 2011). Cromwell et al (1989) observed a 40-g increase in piglet birth weight when gilts and sows were fed an extra 1.4 kg of feed daily during late gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing energy allowance in late gestation may improve piglets' vitality and survival at birth, especially in hyperprolific sows Quiniou et al (2005), and helps maintaining sows' body reserves at parturition, whist reducing backfat loss during lactation (Miller et al 2000). Moreover, Shelton et al (2009) found that additional feed allowance in…”
Section: General Structure Of the Modelmentioning
confidence: 99%